2021
DOI: 10.1007/s13224-021-01558-y
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Analysis to Evaluate Knowledge, Attitude And Practices Among Pregnant Women During COVID-19 Pandemic

Abstract: Objective To assess knowledge, attitude and practices (KAP) towards COVID-19 among pregnant women at a tertiary care hospital. Methods This was a questionnaire-based cross-sectional analysis pertaining to COVID-19 which was conducted at a tertiary care obstetric facility in India among 200 consecutive consenting pregnant women. They were assessed for demographic details and KAP score (knowledge—17 questions, attitude—9 questions and practice—8 questions). Analysis of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 12 publications
5
25
2
1
Order By: Relevance
“…Knowledge, attitudes, and practices (KAP) are crucial in recognizing preventive goals, and for this purpose, we conducted this study among pregnant women in Saudi Arabia. We found a relatively low average score for knowledge (10.36 ± 2.58 out of 19; 54.7%) among the participating women, similar to a study from South Africa conducted in a primary health setting, in which the mean knowledge score was only 43% [20]; however, certain studies have shown a much higher correct knowledge rate among pregnant women in developing countries [13,16]. In our study, high knowledge scores were observed related to the transmission routes of the virus (the frequency of correct responses for air droplets, aerosols, and contaminated surfaces was 96.2%, 48.5%, and 94.7%, respectively).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Knowledge, attitudes, and practices (KAP) are crucial in recognizing preventive goals, and for this purpose, we conducted this study among pregnant women in Saudi Arabia. We found a relatively low average score for knowledge (10.36 ± 2.58 out of 19; 54.7%) among the participating women, similar to a study from South Africa conducted in a primary health setting, in which the mean knowledge score was only 43% [20]; however, certain studies have shown a much higher correct knowledge rate among pregnant women in developing countries [13,16]. In our study, high knowledge scores were observed related to the transmission routes of the virus (the frequency of correct responses for air droplets, aerosols, and contaminated surfaces was 96.2%, 48.5%, and 94.7%, respectively).…”
Section: Resultssupporting
confidence: 84%
“…The majority of participants in our study reported good practices during the pandemic, with 91.7% supporting the idea of avoiding crowded places to prevent the spread of disease and 91.9% considering hand hygiene a good preventative method. Both of these are essential preventative measures, and other studies show similarly good practices among pregnant women [13,25]. However, the approach to vaccination during pregnancy was not encouraging, with 82.5% of women being against it.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations